A phosphotungstic acid self-anchored hybrid proton exchange membrane for direct methanol fuel cells. Issue 49 (3rd May 2016) - Xu, Xin; Wang, Haining; Lu, Shanfu; Peng, Sikan; Xiang, Yan
Abstract : DMFCs based on a phosphotungstic acid self-anchored membrane exhibit comparable performance with that of Nafion212. Abstract : A phosphotungstic acid (HPW) self-anchored hybrid proton exchange membrane (PES/PVP-HPW) is prepared and evaluated in direct methanol fuel cells (DMFCs). The proton conductivity of the hybrid membrane is 0.045 S cm −1 at 25 °C, and reaches 0.078 S cm −1 at 80 °C. The hybrid membrane shows a methanol permeability of 1.65 × 10 −6 cm 2 s −1 . The stability test for the hybrid membrane in 2 M methanol at 50 °C for about 100 h reveals that HPW is well immobilized in the hybrid membrane. The DMFC based on the PES/PVP-HPW hybrid membrane with a thickness of 55 μm exhibits comparable performance of 132 mW cm −2 to that of Nafion212 at 80 °C. The effects of the hybrid membrane thickness and methanol concentration on DMFCs performance are evaluated. The optimal methanol concentration and thickness of the membrane is about 1–2 M and 55 μm, respectively. Furthermore, a 130 h stability test for DMFC with PES/PVP-HPW demonstrates that the hybrid membrane is quite stable, which indicates that PES/PVP-HPW is an attractive low-cost alternative proton exchange membrane to Nafion® for portable power sources.